California low carbon fuel policies and natural gas fueling infrastructure: Synergies and challenges to expanding the use of RNG in transportation. (November 2017) - Scheitrum, Daniel; Myers Jaffe, Amy; Dominguez-Faus, Rosa; Parker, Nathan
Abstract: The emergence of natural gas as an abundant, inexpensive fuel in the U.S. raises the possibility that expanding natural gas infrastructure could enable a transition to other low carbon fuels. We assess how California's existing fuels policies interact with expanding natural gas infrastructure in the state to promote renewable natural gas resource development in the state. We employ a profit-maximizing mixed-integer linear programming optimization to solve for development of natural gas refueling infrastructure incorporating spatial and temporal considerations and estimate the associated expansion in natural gas fuel demand in California. We investigate whether renewable fuel and carbon pollution credit markets create sufficient incentive to promote shifting to renewable natural gas fuel to replace vehicular natural gas demand. An assessment of California's current policies is undertaken and alternative policy options to enhance market efficiency are discussed. These policies include improvements to state regulations of waste disposal, incentives for fleets to shift to sustainable fuel trucks, and mechanisms to lower connection costs for in-state renewable natural gas into the California natural gas pipeline grid. Highlights: Carbon credit markets play a central role encouraging production of RNG. RNG requires a price support of $3.75–$26.00 per mmBTU depending on the source. Fourteen BCF/year of RNG possible with current LCFS credit price. Eighty-three BCF/year of RNG possible with current LCFS plus RFS credit prices. Increasing tipping fees can divert organic matter from landfills to RNG production.